From speech to thought: the neuronal basis of cognitive units in non-experimental, real-life communication investigated using ECoG - Derix, Johanna; Iljina, Olga; Weiske, Johanna; Schulze-Bonhage, Andreas; Aertsen, Ad; Ball, Tonio (Frontiers in Human Neuroscience, 2014)
Exchange of thoughts by means of expressive speech is fundamental to human communication. However, the neuronal basis of real-life communication in general, and of verbal exchange of ideas in particular, has rarely been studied until now. Here, our aim was to establish an approach for exploring the neuronal processes related to cognitive “idea” units (IUs) in conditions of non-experimental speech production. We investigated whether such units corresponding to single, coherent chunks of speech with syntactically-defined borders, are useful to unravel the neuronal mechanisms underlying real-world human cognition. To this aim, we employed simultaneous electrocorticography (ECoG) and video recordings obtained in pre-neurosurgical diagnostics of epilepsy patients. We transcribed non-experimental, daily hospital conversations, identified IUs in transcriptions of the patients’ speech, classified the obtained IUs according to a previously-proposed taxonomy focusing on memory content, and investigated the underlying neuronal activity. In each of our three subjects, we were able to collect a large number of IUs which could be assigned to different functional IU subclasses with a high inter-rater agreement. IU-related responses of brain activity showed significant modulations of the spectral magnitude in high gamma frequencies (70-150 Hz) in mouth motor, language, and higher-order association areas. Neuronal responses specific to different IU subclasses were observed in the inferior parietal and prefrontal cortex. Thus, IU-based analysis of ECoG recordings during non-experimental communication elicited topographically- and functionally-specific effects. We conclude that segmentation of spontaneous real-world speech in linguistically-motivated units is a promising strategy for elucidating the neuronal basis of mental processing during non-experimental communication.